Manajemen Parenting untuk Remaja - -, Sugiyanto (Social Welfare Study Program, 2015)
Teenagers are in the growing age that moves dynamically to seek and establish identity / identities. If this phase is one in the care of the risk, it would be borne by the teens themselves, families, communities and countries.The risks occurring in any ages of teen parenting among others is one of the associations having an impact on early marriage, deviant behavior and drop-out. To reduce the risks that occur in adolescents, it needs management in teen parenting, given the importance of the role of youth as the regeneration of the family and the nation are very high asset value, and the management of parenting adolescents needs to be built with a variety of strategies.Keywords: Manajemen, Parenting, Remaja dan Geografi Tubuh.